As políticas de formação do arte educador no século XXI: o caso da UNESP no Estado de São Paulo - Rocha, Jefferson Alves da [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This paper deals with the training of art educators, focusing on the courses offered at public universities in the state of São Paulo, where, specifically the pedagogical approach of training curricula of grades offered at UNESP, campus of São Paulo and Bauru. In the current situation have been proposed, from training in undergraduate courses, new tasks and responsibilities to work teaching the teacher in order to develop this educational increasingly effective so as to ensure efficient productivity autonomous learner in the process cognitive development in basic education, the teacher being assigned the task of stimulating that process and manage situations of educational work as a way of systematizing knowledge. The research consisted of questioning whether that teacher training allowed contact with the educational resources necessary for teaching, under current conditions assigned by the neoliberal conjuncture educational work of art educator with a view to the formation of aesthetic sensibility of the students from the class working, privileged pupils of public schools, to contribute to establishing the apprehension about the pedagogical training of art educators to confront the reality school, considering the specificity of action of these teachers. Therefore we conducted a desk study of existing legislation and the National Curriculum Guidelines that guide teacher training, correlating them to Pedagogical Policy Projects and curricula of undergraduate courses in Arts Education and / or Visual Arts courses UNESP. The work of desk research, quantitative and analytical, refers strictly pedagogical part, amid restructuring curriculum established by the undergraduate courses in the periods 2003 to 2011, with the promulgation of the CNE/ CP nº. 9 / 2001 and the Resolution CNE/CP n.º 1/2002 and n.º 2/2002... (Complete abstract click electronic access below)

O presente trabalho trata da formação inicial de arte-educadores, enfocando os cursos oferecidos em universidades públicas do estado de São Paulo, no qual, abordamos especificamente a parte pedagógica dos currículos de formação das graduações oferecidas na UNESP, nos campi de São Paulo e de Bauru. Na conjuntura atual têm sido propostas, desde a formação nos cursos de graduação, novas tarefas e responsabilidades ao trabalho pedagógico ao professor, no sentido de que este desenvolva ações educativas cada vez mais eficazes de modo a garantir a eficiência da produtividade autônoma do aluno no processo de desenvolvimento cognitivo na Educação Básica, sendo atribuído ao professor à tarefa de estimular tal processo e a gerir situações de trabalho educativo como forma de sistematização do conhecimento. A problematização da pesquisa consistiu se essa formação docente possibilitou o contato com os recursos pedagógicos necessários para o magistério, sob as condições atuais atribuídas pela conjuntura neoliberal ao trabalho educativo do arte-educador com vistas para a formação da sensibilidade estética dos alunos, oriundos da classe trabalhadora, alunado privilegiado das escolas públicas, estabelecendo como objetivo contribuir para a apreensão sobre a formação pedagógica dos arte-educadores para o enfrentamento da realidade escolar, considerando as especificidades de atuação destes professores. Para tanto realizamos um estudo documental da legislação vigente e das Diretrizes Curriculares Nacionais que orientam a formação docente, correlacionando-os aos Projetos Político Pedagógicos e as grades curriculares dos cursos de graduação em Educação Artística e/ou Artes Visuais nos cursos da UNESP. O trabalho de pesquisa documental, quantitativa e analítica, refere-se estritamente a parte pedagógica, em meio aos processos de reestruturação curriculares... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Ensino superior; Professores; Profissionalismo; Curriculos - Avaliação; Avaliação educacional; Education, Higher; São Paulo (Estado) - Ensino superior